2021
DOI: 10.21873/anticanres.15510
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3 Sigma Protein Contributes to Hepatocyte Growth Factor-mediated Cell Proliferation and InvasionviaMatrix Metalloproteinase-1 Regulation in Human Gastric Cancer

Abstract: Background/Aim: The 14-3-3 protein family has a variety of functions in cellular responses in different organisms, including cell-cycle regulation, apoptosis, and malignant transformation. induces G2 arrest, which enables repair of damaged DNA. The purpose of this study was to identify the role of 14-3-3σ up-regulation by hepatocyte growth factor (HGF) in cancer cell proliferation and invasion in gastric cancer. Materials and Methods: In this study, cell culture, western blotting, real-time polymerase chain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In addition, some studies believe that vulnerable plaque will gradually increase in the late stage of atherosclerosis in some ACS patients, which will promote the increase of MMPs expression level in individual serum, further regulate more inflammatory factors, aggravate the individual inflammatory response, and increase the instability of vulnerable plaque (18)(19)(20). In addition, it has been proposed that the secretion of MMPs by fibroblasts is also affected by EMMPRIN, and the analysis of a large number of inflammatory diseases shows that the overexpression of EMMPRIN can significantly increase the expression level of individual MMPs (21,22). As a kind of chronic inflam-mation, the occurrence of atherosclerosis in patients with ACS is also affected by EMMPRIN, and some studies have found that, under the stimulation of inflammatory factors, the expression of EMMPRIN shows a gradual upward trend, and under this influence, the expression of MMPs in patients' serum also shows a rising trend (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies believe that vulnerable plaque will gradually increase in the late stage of atherosclerosis in some ACS patients, which will promote the increase of MMPs expression level in individual serum, further regulate more inflammatory factors, aggravate the individual inflammatory response, and increase the instability of vulnerable plaque (18)(19)(20). In addition, it has been proposed that the secretion of MMPs by fibroblasts is also affected by EMMPRIN, and the analysis of a large number of inflammatory diseases shows that the overexpression of EMMPRIN can significantly increase the expression level of individual MMPs (21,22). As a kind of chronic inflam-mation, the occurrence of atherosclerosis in patients with ACS is also affected by EMMPRIN, and some studies have found that, under the stimulation of inflammatory factors, the expression of EMMPRIN shows a gradual upward trend, and under this influence, the expression of MMPs in patients' serum also shows a rising trend (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…p53 arrests the cell cycle in the G2/M phase by transcriptionally activating 14‐3‐3σ, and plays a role in the response of cells to DNA damage 211,212 . 14‐3‐3‐σ, also known as stratifin, is mainly found in stratified epithelial cells.…”
Section: Regulatory Mechanisms Of P53 On Downstream Genesmentioning
confidence: 99%
“…p53 arrests the cell cycle in the G2/M phase by transcriptionally activating 14‐3‐3σ, and plays a role in the response of cells to DNA damage. 211 , 212 14‐3‐3‐σ, also known as stratifin, is mainly found in stratified epithelial cells. 14‐3‐3‐σ, a protein encoded by the SFN gene in humans, is involved in cell cycle checkpoint control after DNA damage.…”
Section: Regulatory Mechanisms Of P53 On Downstream Genesmentioning
confidence: 99%
“…Studies have shown that 14-3-3 proteins are essential for cancer development [24][25][26][27][28][29]. 14-3-3 proteins are ubiquitously expressed in eukaryotic cells, and there are seven main protein isoforms in mammals [30].…”
Section: Introductionmentioning
confidence: 99%
“…14-3-3 proteins can bind to other proteins [ 17 , 18 ] and participate in various biological activities, including signal transduction, cell cycle progression, apoptosis, and enzyme activity regulation [ 19 , 20 , 21 , 22 , 23 ]. Studies have shown that 14-3-3 proteins are essential for cancer development [ 24 , 25 , 26 , 27 , 28 , 29 ]. 14-3-3 proteins are ubiquitously expressed in eukaryotic cells, and there are seven main protein isoforms in mammals [ 30 ].…”
Section: Introductionmentioning
confidence: 99%